Chronosequence Effect of Post Tin Mining Ponds to Metals Residu and Microecosystem Change - Andri Kurniawan (Journal Omni-Akuatika, 2017)
The ecological change caused by tin mining activity is among the most important sorts of problem in the environment, including heavy metals contamination and change of microecosystem. This article aim to identify speciation of metals and heavy metals in post tin mining aquatic ecosystem, particularly, disused tin mining ponds in West Bangka, Indonesia in a chronosequence effect study. Speciation of metals and heavy metals are detected by X-Ray Fluorescence. X-Ray Fluorescence analysis show that heavy metals in post tin mining ponds like Fe, Sn, and Cu and also some metals such as Mg, Si, Al, S, and P were detected with a different numbers. There is a speciation of heavy metals and metals in post tin mining ponds with chronosequence effect. It can become an important and basic study about potential bioremediator in the research locations. Further, researches about microecosystem change and interaction of microorganisms and heavy metals there can become an information to design an ecological management tool to manage this ecosystem so it can be used for primay or secondary activity.